Język domu rodzinnego jako rdzenna wartość kreująca tożsamość międzykulturową - Nikitorowicz, Jerzy (Oficyna Wydawnicza ATUT - Wrocławskie Wydawnictwo Oświatowe, 2012)
The thesis which is undertaken in this article applies to a native language (the language of the family and home) as the leading (primary) value of creating a crosscultural identity. To justify this argument, the author refers to his own research and literature in this area. There are many references to the theory of cultural relativism by Sapir-Whorf and the theory of core values by Jerzy Smolicz.The author demonstrates, notices, and highlights that the personal and group identity, analysed in terms of evolutionary (processual), based on the values which are recognised and respected in the family, are shaping and developing cross-cultural identity. The more we recognize, respect and accept your native (family and home) identity, the more we are likely to make an effort to get to know the Other and his culture.
Keywords: home; language; family; values; identity